LESSON STUDY: UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA - Indria Pramesti, Fauziah; Suparni; Sunarni (Department of Mathematics Education, Universitas Kuningan, 2025)
Lesson Study is an activity that involves teachers in designing, implementing, observing, and reflecting on the learning process. This study aims to analyze the application of Lesson Study in an effort to improve the quality of mathematics learning. This research is qualitative research carried out in conjunction with the Introduction to Education Field (PLP) activity from September 9 to October 25, 2024 at SMA Negeri 10 Yogyakarta. The subject of the study is class XI 4 students consisting of 36 students in the 2024/2025 school year. Data were collected through observations, interview, and documentation of the learnin process. The collected data were analyzed using a qualitative descriptive. The results of the study show that each stage of Lesson Study, namely plan, do, and see, has been carried out in 2 cycles well. At the plan stage, the model teacher arranges learning tools as needed. Furthermore, in the do stage, the model teacher implements a learning plan that includes preliminary activities, core activities, and closing activities. Finally, in the see stage, the model teacher and the observer conduct reflection to evaluate the success and improvement of learning. The results of the study also showed an improvement in the quality of mathematics learning. The improvement indicator can be seen from the increase in student activity during the learning process and the increase in student learning outcomes. These findings show that the implementation of the right learning strategies can have a positive impact on the quality of mathematics learning in the classroom.